Analyzing global inequality in access to energy: Developing policy framework by inequality decomposition. (15th February 2022) - Sinha, Avik; Balsalobre-Lorente, Daniel; Zafar, Muhammad Wasif; Saleem, Muhammad Mansoor
Abstract: Energy poverty is a critical policymaking problem in the world, while the outlined solutions in academic and policy literature talks about the solutions, without addressing the possible cause of the problem. The interaction between labor and energy market might pave a way to address the issue. Within the context of energy poverty, this interaction might turn out to be a major roadblock in the way to attain the objectives of Sustainable Development Goals (SDGs). From this perspective, this study aims at analyzing the constituents of inequality in access to energy, and in that pursuit, it has employed Kaya-Theil Decomposition method. The study is carried out at the global level over the period of 1990–2019. The study outcomes demonstrate all the inequality components to be rising during the study period. Presence of a possible feedback loop in the association might create the Vicious Circle of Energy Poverty around the globe. This study contributes to the literature by addressing the demand-side dimension of the energy poverty issue, while using the Kaya-Theil Decomposition method as an estimator of demand-side factors. Based on the study outcomes, a policy framework has been recommended, and it is aimed at helping the nations to achieve the objectives of SDG 7, SDG 8, and SDG 10. Graphical abstract: Image 1 Highlights: Constituents of inequality in access to energy in analyzed. Study is done at the global level over 1990–2019. Theil index and Kaya-Theil Decomposition mechanisms are used. Inequality components of inequality in access to energy are rising. Vicious Circle of Energy Poverty might arise by the feedback loop.